SIFAT MEKANIK DAN MORFOLOGI PLASTIK BIODEGRADABLE DARI LIMBAH TEPUNG NASI AKING DAN TEPUNG TAPIOKA MENGGUNAKAN PEMLASTIK GLISEROL - Andri Cahyo Kumoro; Aprilina Purbasari (Diponegoro University, 2014)
[Title: Mechanical Properties and Morfology of Biodegradable Plastic from Steamed Rice Waste and Cassava Flour with Glycerol as Plasticizer] The annual consumption of plastic packaging has increased significantly as a response to the increase of people’s need and buying power. As a packaging material, plastic is light, flexible, practical and inexpensive. Unfortunately, if the plastic is not biodegradable and dumped irresponsibly to the ecosystem may cause serious environmental problems. The objective of this research was to study the effect of glycerol on the characteristic of biodegradable plastic from steamed rice waste and cassava flours composites. The biodegradable plastic was manufactured by casting the warm solution of flours composite with addition of glycerol as plasticizer. The results showed that biodegradable plastic obtained from steamed rice waste and cassava flours composites has limited mechanical stress, but remains flexible in nature. Good quality biodegradable plastic was obtained when 15% weight of glycerol in addition to 30:70 ratio of steamed rice waste flour to cassava flour with tensile strength 20.65 MPa, elongation at break 4.7% and Young Modulus 1138 MPa. The biodegradable plastic exhibits discontinue microstructure, rough and porous. Fourier transform infrared analysis proved the existence of OH, CH2, amide III and amida I groups in the biodegradable plastic.